Hubungan Waktu Tanggap Perawat Dengan Outcome Awal Pasien Kritis Di Instalasi Gawat Darurat - Ernawati; Tri Mawarni; Wahyu Asnuriyati (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Nurse response time is one of the key factors in determining the outcomes of critically ill patients in the emergency department (ED). The faster the nurse responds to an emergency situation, the greater the patient’s chances of survival and recovery. A study by Munah (2020) showed that a delay of more than five minutes in response time for cardiac arrest patients in the ED increased the risk of death by up to 30%. This finding highlights the critical importance of speed in managing critically ill patients. As frontline healthcare providers in the ED, nurses have a major responsibility to ensure that critically ill patients receive prompt and appropriate initial care. Therefore, nurse response time has become a key quality indicator of ED services. However, in practice, many factors influence nurse response time, such as simultaneous arrival of multiple patients, limited nursing staff, work fatigue, and insufficient training and experience in handling critical cases.